Adams' American Railway Accounting - Cunningham, W. J.; Adams, Henry C. (Quarterly Journal of Economics, 1918)
Journal Article Adams' American Railway Accounting Get access W. J. Cunningham W. J. Cunningham Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 33, Issue 1, November 1918, Pages 183–187, https://doi.org/10.2307/1885014 Published: 01 November 1918